Can rectal tube be used instead of ileostomy in patients undergoing rectal resection after neoadjuvant chemo-radiotherapy? (Annals of Medical Research, 2021)
Aim: Neoadjuvant chemo-radiotherapy and total mesorectal excision have become the standard treatment for locally advanced middle and distal rectal cancers. These types of patients carry a serious risk of anastomosis leakage. While the commonly technique is diverting ileostomy; rectal tube placement, with lower morbidity, has also been used in recent years. The aim of this study was to compare the results of ileostomy and rectal tube administration following rectal resection after neoadjuvant therapy.Material and Methods: We retrospectively reviewed the data from 25 patients with rectal cancer who received neoadjuvant chemo-radiotherapy between 2013 and 2019. Patients were evaluated in two groups: ileostomy and rectal tube. Demographic data, operative findings, pathological results, and follow-up information were evaluated.Results: Twelve were in the rectal tube group and 13 were in the ileostomy group. There was no difference between the two groups in terms of tumor location in preoperative data. Patients with hepatic metastasis were found in the ileostomy group, while there were no such patients in the rectal tube group. The operation time (452±128 vs. 295±102 min, p=0.002) and blood loss (485±264 vs 105±80 ml, p=0.0001) were higher in the ileostomy group. The intraoperative complications of the patients were similar in the two groups, whereas the postoperative complications were higher in the ileostomy group (69%-25%, p=0.04). The mean follow-up period was 23.2±18.5 months. The total complication rate due to ileostomy was 20% and the stomata of 15% of the patients were not closed. The cosmetic scores of the patients were better in the rectal tube group (9.8±0.3 vs. 6.3±1.7, p=0.0001). Conclusion: The results of the rectal tube technique were not worse than those of the ileostomy technique in rectal cancers receiving neoadjuvant therapy and this technique may be preferred in appropriate cases.
Keywords: Minimally invasive surgery; laparoscopic colorectal; colon cancer; low anterior; J pouch; colectomy; transanal; loop; diverting; NOSE